The level of awareness towards environmental issues and concern among students in tertiary level: Case study of universities students in Kuala Lumpur and Klang Valley of Malaysia. - Ibrahim, Aishah Nadrah; Bachok, Syahriah; Mohamed Osman, Mariana (2011)
Environmental education is a way of creating knowledge, understanding, values, attitudes, skills, abilities and awareness among individuals and social groups towards the environment protection. The current study reports on the awareness towards environmental issues and protection among 100 students from International Islamic University Malaysia (IIUM). The students have been assessed through a series of questionnaire in order to capture the most precise and meaningful findings. Besides, the study also has identified level of exposure on environmental issues and knowledge. The result revealed that the level of awareness towards environmental issues and protection among students in tertiary level is at below moderate level. The environmental awareness must be strengthen as students todays are the leaders for tomorrow.